ANALISIS KEMAMPUAN MAHASISWA DALAM PENGAJUAN MASALAH NUMERASI - Muhtarom Muhtarom; Nizaruddin Nizaruddin (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
This research aims to analyze the ability of students in mathematical numeracy problem possing. Research data were collected from students of Mathematics Education Universitas PGRI Semarang. The subjects in this research have good communication skills. Data were collected by means of a written numeration test and task-based interview techniques. The data obtained were coded, simplified, then presented, triangulated and then obtained credible data to draw conclusions. The validity of the data used method triangulation and source triangulation was used to obtain credible data. The data collected were analyzed and reduced to include in the data presentation. Data exposure requires further data reduction, then conclusions are drawn. The results showed that there were still a few students who had all three classifications of problem posing abilities, namely pre-solution posing, within-solution posing, and post-solution posing. Students who have pre-solution posing skills can ask questions based on the data provided and can formulate problem solving. Students who have the ability within-solution posing can write down what is known and asked about the problem, raise supporting questions that are relevant to the problem and arrange solutions for supporting questions and problems that are given correctly. Meanwhile, students who have the ability to post-solution posing can raise similar problems after solving the problems given. Students can also arrange solutions to problems that have been made.